(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Vitamin B12 (cobalamin) plays a crucial role in the development of the central nervous system, myelin synthesis, and DNA biosynthesis. Recent epidemiological and clinical studies indicate that vitamin B12 deficiency in children is associated not only with hematological disorders but also with impairments in cognitive functions and academic performance. Vitamin B12 is a water-soluble vitamin involved in DNA synthesis, erythropoiesis, and the myelination of nerve fibers. Its deficiency, particularly during periods of growth and development, can have a significant impact on central nervous system function. According to recent scientific evidence, vitamin B12 deficiency remains a global public health concern among children, especially in low- and middle-income countries where its prevalence is higher. B12 deficiency disrupts the process of myelin formation, leading to slowed nerve impulse conduction and subsequent decline in cognitive functions.